IMPLEMENTASI TOTAL QUALITY MANAGEMENT SEBAGAI SOLUSI PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM DI ERA REVOLUSI INDUSTRI 4.0 - Imam Syafi’i; Lailatul Fitriyah (Nurul Jadid University, 2020)
Indonesian in this decade is being echoed about the Industrial Revolution 4.0 which undeniably has big impact on the world of education. The impact of disruptive innovation in the Industrial Revolution 4.0 era forced education to make new innovations by utilizing technology, including Islamic Educational Institutions. The development of management is the right step to advance the sector of Islamic education Institutions so that they can compete whith other schools. Implementation of Total Quality Management in Islamic Education Institutions that focus on quality assurance can be a solution. Quality assurance emphasizes that education is not only focused on products but also the process in making products. By carrying out the principle of custamer satisfaction or service user in this case students, parents and the community in general the presence of Quality-based management will make the branding image of Islamic Education Institutions increase in the eyes of the community. For this reason, the cooperation of each party has greatly contributed to success of Total Quality Management in Islamic Education Institution